Molecular characterization of Helicotylenchus multicinctus and H. dihystera (Tylenchida: Hoplolaimidae) from Theobroma cacao in Nigeria - Daramola, Fisayo Y.; Orisajo, Samuel B.; Malan, Antoinette P.; Marais, Mariette (Zootaxa, 2020)
The genus Helicotylenchus contains cosmopolitan, ubiquitous plant-parasitic nematodes with some species capable of causing significant economic damage to agricultural crops. Accurate species identification in this genus is essential in recognizing the damaging species and establishing effective management options. In a study on cocoa plantations in Nigeria, two species of spiral nematodes were found in high numbers from soil samples obtained from a six-decade old cocoa plantation at the Cocoa Research Institute of Nigeria. An integrated approach involving a combination of morphology, morphometrics, and molecular tools was used to identify the nematode species. Morphological data indicate the presence of both H. multicinctus and H. dihystera. There is congruence in the morphological and molecular data obtained for H. multicinctus. However, phylogenetic analysis of the 28S rDNA expansion segment revealed a high variability in the sequences of the Nigerian population of H. dihystera, suggesting the need for a careful appraisal and more comparative studies.